Ancaman invasi acacia decurrens pascaerupsi gunungapi merapi 2010 terhadap pemulihan keanekaragaman hayati flora pegunungan di taman nasinal gunung merapi. - , Betti Yuniasih ([Yogyakarta] : Universitas Gadjah Mada, 2013)
After the Merapi volcano eruption in 2010, the invasion of Acacia decurrens was considered as a threat to restoration of mountain flora biodiversity in Gunung Merapi National Park (GMNP). Aims of this research were to know the spatial and temporal distribution of Acacia decurrens in GMNP and to know the ecological disturbance that disturbs the restoration of mountain flora biodiversity. The research conducted in the second year after the Merapi volcano eruption by comparing 2 locations: the location that was affected by pyroclastic flow in Glagaharjo and the location that was not affected by pyroclastic flow in Tegalmulyo. The ecological approach combined with geo-information system used as method in this research to provide information about the vegetation structure and the spatial distribution. The results showed that the NDVI value in the location affected by pyroclastic flow in second year after eruption is 0,702 which is almost the same as the NDVI index in the control location that was not affected by pyroclastic flow which is 0,696. Based on the canopy interpretation and field survey results, it is indicated that Acacia decurrens is the dominant species in the plant succession after the Merapi volcano eruption in 2010. The result of the vegetation analysis showed that the A.decurrens growing in the GMNP were in the sapling growth stage with the important value index of 288,96%. The dominancy of A.decurrens in the location affected by pyroclastic flow is a high-level threat to the restoration of mountain flora biodiversity, but in the other hand A.decurrens is also have potential as a pioneer species in the succession. The threat posed by of A.decurrens is because it invaded the mountain flora habitat and became strong competitor in getting light, water, and nutrient. In addition to the threat from A.decurrens, the human activity in GMNP is also the ecological disturbance to natural plant succession.